Loss of Parp7 increases type I interferon signalling and reduces pancreatic tumour growth by enhancing immune cell infiltration - Kannen, Vinicius; Rasmussen, Marit; Das, Siddhartha; Giuliana, Paolo; Izzati, Fauzia N.; Choksi, Hani; Erlingsson, Linnea A. M.; Olafsen, Ninni E.; Åhrling, Samaneh S.; Cappello, Paola; Teino, Indrek; Maimets, Toivo; et al. (Frontiers in Immunology, 2025)
BackgroundPancreatic ductal adenocarcinoma (PDAC) is one of the most lethal forms of cancer, and despite low incidence rates, it remains the sixth leading cause of cancer related deaths worldwide. Immunotherapy, which aims to enhance the immune system’s ability to recognize and eliminate cancer cells, has emerged as a promising approach in the battle against PDAC. PARP7, a mono-ADP-ribosyltransferase, is a negative regulator of the type I interferon (IFN-I) pathway and has been reported to reduce anti-tumour immunity.MethodsWe used murine pancreatic cancer cells, CR705, CRISPR/Cas9, in vivo tumour models and spectral flow cytometry to determine the role of PARP7 in pancreatic tumour growth.ResultsLoss of Parp7 elevated the levels of interferon stimulated gene factor 3 (ISGF3) and its downstream target genes, even in the absence of STING. Cancer cells knocked out for Parp7 (CR705Parp7KO) produced smaller tumours than control cells (CR705Cas9) when injected into immunocompetent mice. Transcriptomic analyses revealed that CR705Parp7KO tumours had increased expression of genes involved in immunoregulatory interactions and interferon signalling pathways. Characterization of tumour infiltrating leukocyte (TIL) populations showed that CR705Parp7KO tumours had higher proportions of natural killer cells, CD8+ T cells and a lower proportion of anti-inflammatory macrophages (M2). The overall TIL profile of CR705Parp7KO tumours was suggestive of a less suppressive microenvironment.ConclusionsOur data show that loss of Parp7 reduces PDAC tumour growth by increasing the infiltration of immune cells and enhancing anti-tumour immunity. These findings provide support to pursue PARP7 as a therapeutic target for cancer treatment.